The Amish midwife's secret - Good, Rachel J. (Good, Rachel J. Love & promises, 2018)
Kyle Miller never planned on becoming a country doctor. But when he's offered a medical practice in his sleepy hometown, Kyle knows he must return... and face the painful past he left behind. Except the Amish community isn't quite ready for Kyle. Especially the pretty midwife who refuses to compromise her traditions with his modern medicine... The more Leah Stoltzfus works with the handsome Englisch doctor, the more she finds herself caught between the expectations of her family and her own hopes for the future. It will take one surprising revelation and one helpless baby in need of love to show Leah and Kyle that their bond may be greater than their differences... if Leah can find the courage to follow her heart.